A new species of Araucnephia (Diptera: Simuliidae) from the Northeast Region of Brazil - Pessoa, Felipe Arley Costa; Ríos-Velásquez, Claudia María; Py-Daniel, Victor (Zootaxa, 2012)
We describe and illustrate the pupa, larva, and both adults of a new species in the genus Araucnephia Wygodzinsky &Coscarón, 1973 (A. cearensis nov. sp.). The species was found in a highland area in Ceará State, Northeast Brazil. The pupa canbe separated from those of other Araucnephia pupae based on the number of gill filaments, which range from 25 to 35 branches(versus 9 or 14), and by it being completely encased by the cocoon. The larva can be separated from those of other Araucnephiabased on the presence of a median accessory anal sclerite. Adults are typical of the genus. This species extends the northern range of the genus Araucnephia, which is postulated to be Gondwanan in origin.